Mekanisme Penyelesaian Sengketa Tanah terhadap Hak Milik Perorangan menurut Peraturan Menteri ATR/BPN No 21 Tahun 2020 tentang Penanganan dan Penyelesaian Kasus Pertanahan - Yusril Ihza Mahendra; Herdy Pratama Susantyo (AHKAM, 2025)
This study is motivated by the limited research on mechanisms for resolving land disputes over individual ownership rights, despite the significant impact of such issues on legal certainty and social stability in Indonesia. The objective is to analyze the implementation of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency (Permen ATR/BPN) No. 21 of 2020 in resolving land disputes and providing legal protection for individual landowners. The research employed a normative juridical method, using data sources comprising legal documents, statutory regulations, and case studies selected through purposive sampling. Data were collected through literature review and document analysis, then examined descriptively and qualitatively using a statutory approach. The findings show that the regulation provides three primary dispute resolution mechanisms, mediation, conciliation, and litigation with priority given to amicable settlements before resorting to court proceedings. These mechanisms enhance efficiency, reduce conflict escalation, and safeguard individual property rights in line with the principle of legal certainty. The study concludes that the application of Permen ATR/BPN No. 21 of 2020 plays an important role in streamlining administrative procedures and strengthening the legal protection of landowners. Its implications include theoretical contributions to land law literature and practical recommendations for policymakers, land authorities, and legal practitioners to clarify procedures, strengthen mediation capacity, and raise public awareness, while also opening opportunities for further research on the long-term effectiveness of non-litigation dispute resolution.